THE INFLUENCE OF INTELLECTUAL CAPITAL ON THE MARKET VALUE AND FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Abdul Rasyid (Sean Institute, 2023)
This study aims to examine the impact of Intellectual Capital on the market value and financial performance of publicly traded companies on the Indonesia Stock Exchange (BEI).